(3eLdI cdjI GdJQHjI HGdefUhQI (B/s - (3LGeYI GdefUhQI (B((3eUQ(B).s (3cdjI GdJQHjIs ((3GdefUhQI (B:s (3LGeYI GdefUhQI,s, 2010)
(3aj eLGd GdYdhe GdEfSGfjI(B.s
(3GdhUa eCNhP ef (B: (3Y (B73 (3L (B1 ((3eGjh (B2010)s
(3WQjbI GdhUhd (B: (3THcI GdEfJQfJ(B.s
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjI(B.s
Keywords: (3GdJQHjIs -- (3OhQjGJs